|aTesting nonlinear New Economic Geography models - Eckhardt Bode; Jan Mutl (Institute for Advanced Studies (IHS), 2010)
We test a New Economic Geography (NEG) model for U.S. counties, employing a new strategy that allows us to bring the full NEG model to the data, and to assess selected elements of this model separately. We find no empirical support for the full NEG model. Regional wages in the U.S. do not respond to local wage shocks in the way predicted by the model. We show that the main reason for this is that the model does not predict either the migration patterns induced by local wage shocks or the repercussions of this migration for regional wages correctly.
Keywords: C21; C51; R12; 330; New Economic Geography; spatial econometrics